If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(6 + -1x) = 89 (6 * 2x + -1x * 2x) = 89 (12x + -2x2) = 89 Solving 12x + -2x2 = 89 Solving for variable 'x'. Reorder the terms: -89 + 12x + -2x2 = 89 + -89 Combine like terms: 89 + -89 = 0 -89 + 12x + -2x2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. 44.5 + -6x + x2 = 0 Move the constant term to the right: Add '-44.5' to each side of the equation. 44.5 + -6x + -44.5 + x2 = 0 + -44.5 Reorder the terms: 44.5 + -44.5 + -6x + x2 = 0 + -44.5 Combine like terms: 44.5 + -44.5 = 0.0 0.0 + -6x + x2 = 0 + -44.5 -6x + x2 = 0 + -44.5 Combine like terms: 0 + -44.5 = -44.5 -6x + x2 = -44.5 The x term is -6x. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6x + 9 + x2 = -44.5 + 9 Reorder the terms: 9 + -6x + x2 = -44.5 + 9 Combine like terms: -44.5 + 9 = -35.5 9 + -6x + x2 = -35.5 Factor a perfect square on the left side: (x + -3)(x + -3) = -35.5 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 2(n-3)=-2+-9 | | -1+4x=-77 | | 15f+6-1f=2f-6 | | 7x-1=2x-4 | | 13t-4(2t-5)=15 | | 16y^3-4y^2-2y=0 | | 2n-6*4=5 | | (3x-7)-5=12 | | 22x=35 | | 12x=37 | | 18x-32=28x/2 | | 1w+2w=24 | | -1a=9 | | 7x+4x=8 | | 7x+7-6x=6 | | 7(x-3)-2x= | | y^3-12y^2+32=0 | | -6(m+1)-2c=24 | | 2x^6-x^4-2x^2+4=0 | | 1.14x=1.25 | | x^2+4=x+4 | | 0.25x=0.275 | | -9+16x=5x+13 | | (2x-9)+3x=16 | | 30-(-2)(4-x)= | | X+19+2x=-18-2x-23 | | 4(-0.142+-0.285y)=-13 | | (x-17.5)*9.5=8.085 | | 30-(2)(4-x)= | | 13.61=142.56x^6-635.47x^5+1196.7x^4-1235.9x^3+752.4x^2-261.81x+43.991 | | (x-17.5)*9.5=1.415 | | ifx+6=3thenx |